2020
DOI: 10.3390/cells9020523
|View full text |Cite
|
Sign up to set email alerts
|

MYC’s Fine Line Between B Cell Development and Malignancy

Abstract: The transcription factor MYC is transiently expressed during B lymphocyte development, and its correct modulation is essential in defined developmental transitions. Although temporary downregulation of MYC is essential at specific points, basal levels of expression are maintained, and its protein levels are not completely silenced until the B cell becomes fully differentiated into a plasma cell or a memory B cell. MYC has been described as a proto-oncogene that is closely involved in many cancers, including le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 183 publications
0
30
0
Order By: Relevance
“…The ability to monitor both this signaling and transcriptional regulation is necessary to enable fundamental research on wanted B cell responses against pathogens and unwanted B cell responses, as observed in autoimmune diseases [37][38][39] or during allo-antibody formation after blood transfusion [40]. Additionally, transcriptional dysregulation and overactivated signaling pathways can lead to B cell malignancies [41,42]. Finally, it can aid in the development and characterization of therapeutic inhibitors for a range of diseases [43].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to monitor both this signaling and transcriptional regulation is necessary to enable fundamental research on wanted B cell responses against pathogens and unwanted B cell responses, as observed in autoimmune diseases [37][38][39] or during allo-antibody formation after blood transfusion [40]. Additionally, transcriptional dysregulation and overactivated signaling pathways can lead to B cell malignancies [41,42]. Finally, it can aid in the development and characterization of therapeutic inhibitors for a range of diseases [43].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to monitor both this signaling and transcriptional regulation is necessary to enable fundamental research on wanted B cell responses against pathogens and unwanted B cell responses as observed in autoimmune diseases [38][39][40] or during allo-antibody formation after blood transfusion [41]. Additionally, transcriptional dysregulation and overactivated signaling pathways can lead to B cell malignancies [42,43]. Finally, it can aid in the development and characterization of therapeutic inhibitors for a range of diseases [44].…”
Section: Introductionmentioning
confidence: 99%
“…MYC promotes B cell proliferation and differentiation by activating several B cell determining genes, such as Cd19 [ 33 , 34 , 35 , 36 , 37 ]. Immature B cells expressing a complete, functional, non-autoreactive BCR downregulate MYC expression, enter the peripheral circulation and then accumulate in lymph nodes where further maturation takes place under differential MYC expression [ 38 , 39 ]. MYC is re-expressed after (antigen) activation of the BCR, promoting proliferation and inhibiting differentiation of mature B cells [ 39 , 40 ].…”
Section: The Role Of Myc In Normal B Cell Developmentmentioning
confidence: 99%
“…Immature B cells expressing a complete, functional, non-autoreactive BCR downregulate MYC expression, enter the peripheral circulation and then accumulate in lymph nodes where further maturation takes place under differential MYC expression [ 38 , 39 ]. MYC is re-expressed after (antigen) activation of the BCR, promoting proliferation and inhibiting differentiation of mature B cells [ 39 , 40 ]. After positive selection, MYC expression is downregulated, allowing B cells to differentiate into memory B cells or plasmablasts and to exit the germinal center [ 39 , 41 ].…”
Section: The Role Of Myc In Normal B Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation